A Review of Finite Element Method in Detecting Incipient Faults Occur in Power Transformer - Nor Azizah , Mohd Yusoff; Abdul Karim, Kasrul; Ab Ghani, Sharin (2013)
As one of the particular parts in power system, power transformer needs a serious attention. The responsibility and set up in planning preventive maintenance of transformer is important for ease of restructuring power system diagnosis. Inter-turn short circuit cases are the major fault that drives into severe failures in power transformer. To this end, Finite Element Method (FEM) has been proved to be a potential tool for analyzing the physical behavior of real transformer in the presence of inter-turn faults. This contribution is aimed at obtaining diagnosis throughout justifying the modification of winding frequency response as a result of fault occurrence. Finally, this paper reviews an experimental work by Frequency Response Analysis (FRA) to validate the FEM of the faulty transformer simulation. The result of the experiment is capable to demonstrate the model from FEM to reproduce the real behavior of the transformer with inter-turn winding faults. This may be possibly beneficial for a few jobs which from the illustration of FEM result; it was yield insight into developing several patterns of failures in fault detection of power transformer.